2005
DOI: 10.1016/j.eupc.2005.02.120
|View full text |Cite
|
Sign up to set email alerts
|

Do we need pacemakers resistant to magnetic resonance imaging?

Abstract: Asynchronous pacing due to magnetostatic and gradient fields may be problematic in patients with spontaneous rhythm. To avoid them, PM triggered MRI scan restricted to refractory period is proposed. Neither inhibition of PM nor heating of the electrode poses real risks. So far, we have examined eight patients 12 times in MRI triggered mode without problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 14 publications
0
94
0
10
Order By: Relevance
“…Measurements with a "pacemaker patient simulation model" (described in Ref. 15) in am MRI machine with isolated sinusoidal gradients showed that the waveform is no half sinus wave, as expected under steady state conditions, but resembles a sinus square pulse probably due to the limited frequency response of the gradient coil. Figure 5 demonstrates the waveshape of the induced voltage measured in a 1.5T MRI machine (Philips Gyroscan, Philips Medical Systems, Best, The Netherlands).…”
Section: Investigation Of Experimental Resultsmentioning
confidence: 99%
“…Measurements with a "pacemaker patient simulation model" (described in Ref. 15) in am MRI machine with isolated sinusoidal gradients showed that the waveform is no half sinus wave, as expected under steady state conditions, but resembles a sinus square pulse probably due to the limited frequency response of the gradient coil. Figure 5 demonstrates the waveshape of the induced voltage measured in a 1.5T MRI machine (Philips Gyroscan, Philips Medical Systems, Best, The Netherlands).…”
Section: Investigation Of Experimental Resultsmentioning
confidence: 99%
“…There are only individual reports of complications from case reports of patients who underwent an MR examination without specific safety precautions because the physician was unaware of the presence of a pacemaker/ICD system. This includes at least 7 cases with a fatal outcome [28]. Both the true number of MR-related complications and the reference value, namely the total number of patients who underwent such an "accidental" MR examination, are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Le domaine hospitalier est très particulier : chirurgie (bistouri électrique, ablathérapie), imagerie médicale (IRM), thérapie par stimulation électromagnétique, monitoring... De nombreuses investigations ont été menées sur l'IRM (Achenbach et al, 1997 ;Irnich et al, 2005), qui est devenu un moyen de diagnostic quotidien. Cependant, la présence d'un implant est considérée comme une contre-indication à ce type d'imagerie, contre-indication qui commence à être remise en cause dans un esprit d'évaluation bénéfice/risque du patient.…”
Section: L'environnement Médico-hospitalierunclassified